Portugal : Staff Report for the 2008 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Portugal's 2008 Article IV Consultation highlights that Portugal's financial system remains sound and well supervised. Portugal has accumulated substantial macroeconomic imbalances, and the policy challenge is to smooth the adjustment, containing domestic demand while increasing productivity and flexibility, thus rebalancing growth to the external sector. The weaker global conditions should thus be taken as a reason to strengthen efforts to reignite the stalled convergence process and continue fiscal consolidation and reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet